Co-production of pigment and high value-added bacterial nanocellulose from Suaeda salsa biomass with improved efficiency of enzymatic saccharification and fermentation - Tan, Ran; Sun, Qiwei; Yan, Yiran; Chen, Tao; Wang, Yifei; Li, Jiakun; Guo, Xiaohong; Fan, Zuoqing; Zhang, Yao; Chen, Linxu; Wu, Guochao; Wu, Nan (Frontiers in Bioengineering and Biotechnology, 2023)
This study evaluated the co-production of pigment and bacterial nanocellulose (BNC) from Suaeda salsa biomass. The extraction of the beet red pigment reduced the salts and flavonoids contents by 82.7-100%, promoting the efficiencies of enzymatic saccharification of the biomass and the fermentation of BNC from the hydrolysate. SEM analysis revealed that the extraction process disrupted the lignocellulosic fiber structure, and the chemical analysis revealed the lessened cellulase inhibitors, consequently facilitating enzymatic saccharification for 10.4 times. BNC producing strains were found to be hyper-sensitive to NaCl stress, produced up to 400.4% more BNC from the hydrolysate after the extraction. The fermentation results of BNC indicated that the LDU-A strain yielded 2.116 g/L and 0.539 g/L in ES-M and NES-M, respectively. In comparison to the control, the yield in ES-M increased by approximately 20.0%, while the enhancement in NES-M was more significant, reaching 292.6%. After conducting a comprehensive characterization of BNC derived from S. salsa through Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Thermogravimetric Analysis (TGA), the average fiber diameter distribution of these four BNC materials ranges from 22.23 to 33.03 nanometers, with a crystallinity range of 77% to 90%. Additionally, they exhibit a consistent trend during the thermal degradation process, further emphasizing their stability in high-temperature environments and similar thermal properties. Our study found an efficient co-production approach of pigment and BNC from S. salsa biomass. Pigment extraction made biomass more physically and chemically digestible to cellulase, and significantly improved BNC productivity and quality.